Treatment of staphylococcal septic arthritis in rabbits by systemic antibiotics and intra-articular corticosteroids. Issue 11 (1st November 1998) - Wysenbeek, A J; Volchek, J; Amit, M; Robinson, D; Boldur, I; Nevo, Z
Abstract : OBJECTIVE: To assess the effect of intra-articular corticosteroids added to systemic antibiotics in experimental septic arthritis. METHODS: Rabbits were injected intra-articularely by Staphylococcus epidermidis. Rabbits received no additional treatment and served as control (group 1), were treated with systemic antibiotics (group 2), or treated with systemic antibiotics and intra-articular corticosteroids (group 3). After 15 days animals were killed and joint histopathological-histochemical parameters were assessed. RESULTS: All rabbits survived the experiment. The treated groups (2–3) had lower histological-histochemical scores in comparison with the untreated group (1). Group 3 had significantly lower scores in joint sections in comparison with group 2: (mean (SD) 6.5 (1.4) v 4.0 (1.0), p=0.001 and 7.4 (2.6) v 4.2 (2.2), p= 0.01), because of lower damage expressed in clustering of chondrocytes, pannus formation, proteoglycan depletion, and synovitis. CONCLUSION: Addition of local corticosteroids to systemic antibiotics in septic arthritis seems to be harmless, and improves joint histological-histochemical parameters in this experimental setting.